2018
DOI: 10.2298/vsp161223035g
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne lymphadenopathy acquired in Serbia: Report of two cases

Abstract: Introduction. Acronym tick-borne lymphoadenoathy (TI-BOLA (Dermacentor-borne necrosis erythema and lymphoadenopathy-DEBONEL, scalp eschar associated with neck lymphoadenopathy-SENLAT) comprises clinical diagnosis of tick-borne symptoms of cervical or occipital lymphadenopathy with inoculation eschar at the site of tick bite on scalp. Since the first description, it was proved to be associated with several infectious agents, most frequently Rickettsia slovaca, or less often other spotted fever group Rickettsiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the Balkan peninsula, Turkey is the only country with previous reports of MSF-like illness [1], while MSF cases have been reported in Bulgaria, Croatia, Greece, Romania and Turkey [9][10][11][12][13]. Although MSF is not reported in Serbia, recent reports of tickborne lymphadenopathy [14] and atypical clinical manifestations caused by Rickettsia helvetica [4] indicate circulation of SFGR in the local population.…”
Section: Discussionmentioning
confidence: 99%
“…On the Balkan peninsula, Turkey is the only country with previous reports of MSF-like illness [1], while MSF cases have been reported in Bulgaria, Croatia, Greece, Romania and Turkey [9][10][11][12][13]. Although MSF is not reported in Serbia, recent reports of tickborne lymphadenopathy [14] and atypical clinical manifestations caused by Rickettsia helvetica [4] indicate circulation of SFGR in the local population.…”
Section: Discussionmentioning
confidence: 99%
“…Research on SFG rickettsiae in Serbia has significantly increased in the last two decades. Using IFAT, Samardžić et al [ 170 ] detected seroreactive human blood sera (9/134) against antigens of Rickettsia conorii , while Gajinov et al [ 171 ] described tick-borne lymphadenopathy (TIBOLA) caused by R. slovaca in two female patients after tick bites. In a recent study, Banović et al [ 172 ] described five confirmed, two suspected and two probable SFG rickettsiae infection cases, and reported that molecular analysis showed intra-species variability in R. helvetica strains infecting humans in Serbia.…”
Section: Serbiamentioning
confidence: 99%
“… Human Two cases Mf qPCR [ 157 , 166 , 172 , 175 ] R. helvetica Ixodes ricinus , human 7.4–54.0, two cases (humans) PCR-Seq, mf qPCR [ 163 , 166 , 172 174 ] R. slovaca Haemaphysalis sp. from human One case mf qPCR [ 171 , 172 ] R. conorii Human 1.9–25.0 IFAT [ 170 ] R. aeshlimanii Ixodes ricinus from humans 3.0 mf qPCR [ 163 ] R. acari Human 4.0–10.4 IFAT [ 170 ] R. felis Ixodes ricinus from humans 4.3 mf qPCR, RT-PCR [ 163 , 166 ] Borrelia spp. Ticks from humans 19.35 RT-PCR [ 166 ] B. burgdorferi s.l Human 8.1–54.2 IFAT, ELISA, WB [ ...…”
Section: Introductionmentioning
confidence: 99%
“…Serbia has diverse landscapes, with plains in the north, limestone ranges and basins in the east and mountains and hills in the south and southeast. As in the rest of Europe, the most common and widespread human TBD in Serbia is Lyme borreliosis, along with other less frequently diagnosed diseases such as tick-borne encephalitis, human monocytic ehrlichiosis, tick-borne lymphadenopathy, and Crimean-Congo hemorrhagic fever (CCHF) [ [10] , [11] , [12] , [13] ]. Apart from the endemicity of CCHF [ 14 ], little is known about the impact of TBDs on human health in Serbia.…”
Section: Introductionmentioning
confidence: 99%